Integrating Epidemiological Information into MRI Reports Reduces Ensuing Radiologic Testing Costs Among Patients with Low Back Pain: A Controlled Study. - Weeks, Bill; Pike, Jason; Schaeffer, Christopher J.; Devine, Mathew J.; Ventura, John M.; Donath, Jeremy; Justice, Brian D. (The Joint Commission Journal on Quality and Patient Safety, 2020)
In the United States, spine pain treatment is expensive and increasingly uses guideline discordant evaluation and treatment modalities, including magnetic resonance imaging (MRI), (1) up to 60% of which are considered inappropriate. (2) Inappropriate lumbar MRIs are associated with a short-term cascade of related care costs, (3) potentially causing patient harm. (4)